Identification of Transversal Competences for Curriculum Reform: The Case of Multiculturalism - Diani María Víquez-Moreno; Jaime Ricardo Valenzuela-González; María Dolores Compeán-Aguilar (Revista Electrónica Educare)
This scientific research article presents the results of a research conducted in the field of generic competencies –a new subject driven by the UNESCO in recent years as a way to change the inefficient performance of education systems. It covers the general theory on the subject, but deepens into the Competence to Interact in Multicultural Environments. The aim was to identify a set of qualities that distinguish those people who are skillful at interacting in multicultural environments from those people who are not so skillful. The mixed methods strategy was used –first, with an equitable, sequential and qualitative status and, then, with a quantitative one. The sample included six experts and fifty-two college students who participated in a case study with a semi-structured interview –for the first group; and the implementation of a self-report instrument –for the second group. For the analysis of qualitative data, the process included reduction, display and verification of data. The quantitative phase included three statistical analyses: descriptive, psychometric and relational. The main results are the creation of a profile that allowed promoting educational activities for developing key competencies, and the identification of a methodology suitable for this purpose – beginners’ theory and experts. The most important conclusion is the need to have the current educational systems make curricular changes that build skilled human resources for knowledge society, as well as specific ideas about the development process of the competency, the performance areas, motivations, and the variety of strategies to develop it.